2015
DOI: 10.3174/ajnr.a4300
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular Location as a Risk Factor for Hemorrhage and Severe Clinical Presentation in Pediatric Patients with Untreated Brain Arteriovenous Malformations

Abstract: BACKGROUND AND PURPOSE:The morphologic features of brain arteriovenous malformations differ between children and adults; therefore, our aim was to analyze various features of brain arteriovenous malformations to assess the risk of hemorrhage in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Analyzing the natural history of AVMs, several studies did not show a relationship between location and bleeding risk . Ma et al . analyzed pediatric patients with AVMs seeking risk factors for hemorrhagic presentation and subsequent hemorrhage (follow‐up), obtaining conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the natural history of AVMs, several studies did not show a relationship between location and bleeding risk . Ma et al . analyzed pediatric patients with AVMs seeking risk factors for hemorrhagic presentation and subsequent hemorrhage (follow‐up), obtaining conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…The periventricular brain includes not only a vital structure in the deep brain and brain stem but also important subcortical tracts, which are not classified as either deep brain or eloquent region. Our previous data indicated that 87% of periventricular ruptured bAVMs had parenchymatous hemorrhage with or without intraventricular extension, which could lead to the disruption of important nucleus and/or tracts [8], and parenchymal hemorrhage is associated with increased morbidity in bAVM [3, 18]. These features might explain the reason for higher risk for severe hemorrhage of periventricular bAVM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports identified posterior fossa, eloquent location, and associated aneurysm as potential predictors for severe hemorrhagic presentation in ruptured bAVM [7]. Our recent study in pediatric patients suggested a trend toward poorer neurological function at presentation and more emergency intervention in periventricular bAVM [8]. In this study with follow-up data before treatment, we aimed to (1) assess the neurological function after hemorrhagic presentation and subsequent hemorrhage and at follow-up in children with untreated bAVMs; (2) explore predictive features of severe hemorrhage in pediatric bAVM.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations